The Burial Shroud as Dowry: Discrimination Against Women in the Reality of Minangkabau Custom - Nur Azizah Azizah; Rahmiati rahmiati; Shafra Shafra; Elkhairati; Yustiloviani yustiloviani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
In Nagari Padang Laweh, a dowry in the form of a burial shroud (kain kafan) is determined by customary law. This provision applies to every woman who marries, whether a maiden or a widow. The tradition aims to promote social equality and prevent jealousy among community members. However, from the perspective of Islamic law, women are granted the right to determine their own dowry as a form of respect, appreciation, and protection, as emphasized in Qur’an Surah An-Nisa (4):4. This study aims to analyze the social and legal meanings of the dowry tradition involving a burial shroud in Nagari Padang Laweh, and to examine its compatibility with the principles of dowry (mahr) in Islamic law. The research employs a qualitative approach with normative-descriptive analysis. Data were collected through interviews with customary leaders, religious scholars, and married couples, as well as a review of classical Islamic jurisprudence literature. The findings reveal that although the dowry tradition in the form of a burial shroud is intended to promote social equality, it effectively nullifies women’s rights and neglects their protection, even appearing discriminatory. In Islamic law, the dowry is prescribed as something possessing economic value and utility, symbolizing honor and recognition of a woman, and she is granted the right to determine its form. Therefore, the dowry tradition involving a burial shroud is categorized as an ‘urf fasid (corrupt custom) because it contradicts the objectives of Islamic law in upholding the rights and dignity of women within marriage.